Effect of Hysterectomy on Colonoscopy Completion Rate. (2010) - Lacasse, Mélanie; Dufresne, Geneviève; Jolicoeur, Emilie; Rochon, Luc; Sabbagh, Charles; Deneault, Jocelyn; Walsh, Valérie; Gaboury, Isabelle; Hassard, Philip
Abstract : BACKGROUND: Several studies show that colonoscopies are technically more difficult to perform in women than men, especially in women who have undergone abdominal and gynecological surgeries. A review of the literature indicates an increased rate of noncompletion of colonoscopies in most cases; however, no studies have investigated the procedural complication rate, sedation requirements and perception of pain in colonoscopies. OBJECTIVE: To determine whether women who have undergone a previous hysterectomy have a higher noncompletion rate when undergoing a colonoscopy, and to assess whether there is a higher percentage of complications. Furthermore, the present study also aimed to ascertain whether these women required more sedation and whether their perception of pain is greater than that of women who did not undergo previous abdominal surgeries. METHODS: The present study was a prospective cohort study of women, 45 to 80 years of age, who underwent colonoscopy (n=508). A total of 229 patients were eligible for the study; they completed a questionnaire, and were subsequently divided into control and hysterectomy groups. Gastroenterologists performed all procedures. After colonoscopy, the patient and endoscopist completed a pain perception questionnaire. Cecal intubation rates were also recorded. RESULTS: No significant difference for cecal intubation rates were detected between the two groups (95.7% and 98.7% in hysterectomy and control groups, respectively; P=0.176). The crude OR for the success rate was 0.29 (95% CI 0.05 to 1.90). There was no significant difference between groups regarding sedation or the type of colonoscope. No correlation between the gastroenterologists' evaluation of pain and patients' pain was observed. CONCLUSION: Hysterectomy did not significantly diminish the cecal intubation rate, and there was no detectable difference in pain perception or sedative dose. Colonoscopy remains an excellent screening and diagnostic tool for all women.